The COVID-19 Pandemic's Evolving Impacts on the Labor Market: Who's Been Hurt and What We Should Do - Brad J. Hershbein; Harry J. Holzer (Institute of Labor Economics (IZA), 2021)
In this paper, we shed light on the impacts of the COVID-19 pandemic on the labor market, and how they have evolved over most of the year 2020. Relying primarily on microdata from the CPS and state-level data on virus caseloads, mortality, and policy restrictions, we consider a range of employment outcomes – including permanent layoffs, which generate large and lasting costs – and how these outcomes vary across demographic groups, occupations, and industries over time. We also examine how these employment patterns vary across different states, according to the timing and severity of virus caseloads, deaths, and closure measures. We find that the labor market recovery of the summer and early fall stagnated in late fall and early winter. As noted by others, we find low-wage and minority workers are hardest hit initially, but that recoveries have varied, and not always consistently, between Blacks and Hispanics. Statewide business closures and other restrictions on economic activity reduce employment rates concurrently, but do not seem to have lingering effects once relaxed. In contrast, virus deaths – but not caseloads – not only depress current employment, but produce accumulating harm. We conclude with policy options for states to repair their labor markets.
Keywords: J0; J1; J6; 330; COVID-19; pandemic; employment; low-wage workers; state closures